2021
DOI: 10.36227/techrxiv.14345534.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blockchain for Waste Management in Smart Cities: A Survey

Abstract: Smart cities have the potential to overcome environmental problems caused by improper waste disposal to improve human health, protect the aquatic ecosystem, and reduce air pollution. However, today's systems, approaches, and technologies leveraged for waste management are manual and centralized that make them vulnerable to manipulation and the single point of failure problem. Also, a large portion of the existing waste management systems within smart cities fall short in providing operational transparency, tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Recycling rewarding 2, 3,4,6,8,9,10,14,18,20,25,2 8,29,3033,35,36,37,38,39 Recycling supervision 3,8,9,10,16,18,20,25,27,28,2 9,30,33,35,37,38,39,41,42 Service transformation Strategic consideration 8,10,15,19,21,36,37,38,39,4 5 Recycling process optimisation 3, 5,7,9,12,13,18,19,21,22,25 ,26,27, 28,29,30,32,35,36,37,38,39 4,14,18,29,30,31,35,36,39,41,42,43,45 Privacy issue 1,4, 14,18,…”
Section: Behaviour Channelisationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recycling rewarding 2, 3,4,6,8,9,10,14,18,20,25,2 8,29,3033,35,36,37,38,39 Recycling supervision 3,8,9,10,16,18,20,25,27,28,2 9,30,33,35,37,38,39,41,42 Service transformation Strategic consideration 8,10,15,19,21,36,37,38,39,4 5 Recycling process optimisation 3, 5,7,9,12,13,18,19,21,22,25 ,26,27, 28,29,30,32,35,36,37,38,39 4,14,18,29,30,31,35,36,39,41,42,43,45 Privacy issue 1,4, 14,18,…”
Section: Behaviour Channelisationmentioning
confidence: 99%
“…Organisational readiness 4, 18,30,39,45 Stakeholder acceptance 1,4, 14,16,30,39,45 Stakeholder commitment 4,8,14,16,30,39,45…”
Section: Organisational Dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thorough conceptual modeling and deductive analysis revealed that blockchain technology possesses attributes that can enable transparent, tamper-proof, decentralized tracking of e-waste flows across the supply chain in a manner that satisfies the core compliance criteria mandated by Islamic jurisprudence [10]. As elucidated by Leng, J.…”
Section: A Comprehensive Methodology Developed For Analyzing and Ensu...mentioning
confidence: 99%